2018
DOI: 10.3389/fimmu.2018.02412
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRAFs in Signaling Pathways Controlling T Follicular Helper Cell Differentiation and T Cell-Dependent Antibody Responses

Abstract: Follicular helper T (TFH) cells represent a highly specialized CD4+ T cell subpopulation that supports the generation of germinal centers (GC) and provides B cells with critical signals promoting antibody class switching, generation of high affinity antibodies, and memory formation. TFH cells are characterized by the expression of the chemokine receptor CXCR5, the transcription factor Bcl-6, costimulatory molecules ICOS, and PD-1, and the production of cytokine IL-21. The acquisition of a TFH phenotype is a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 227 publications
(386 reference statements)
1
11
0
Order By: Relevance
“…Similarly, our previous study also showed that activation of GITR by GITRL could promote the differentiation of Tfh cells ( 19 ). Mechanically, GITR triggering initiated downstream canonical nuclear factor-κB (NF-κB) pathway through recruitment of tumor necrosis factor receptor-associated factor 2 (TRAF2) and TRAF5, which was responsible for B-cell lymphoma 6 (Bcl-6) transcription in Tfh cell program ( 24 ). Notably, a recent study identified the regulation of GITR signaling on Tfh cells in anti-tumor immune responses.…”
Section: Effect Of Gitr On Effector T Cellsmentioning
confidence: 99%
“…Similarly, our previous study also showed that activation of GITR by GITRL could promote the differentiation of Tfh cells ( 19 ). Mechanically, GITR triggering initiated downstream canonical nuclear factor-κB (NF-κB) pathway through recruitment of tumor necrosis factor receptor-associated factor 2 (TRAF2) and TRAF5, which was responsible for B-cell lymphoma 6 (Bcl-6) transcription in Tfh cell program ( 24 ). Notably, a recent study identified the regulation of GITR signaling on Tfh cells in anti-tumor immune responses.…”
Section: Effect Of Gitr On Effector T Cellsmentioning
confidence: 99%
“…TRAF3 belongs to the TRAF family of proteins that are known as intracellular adaptors and E3 ubiquitin ligases mediating receptor-based signaling [13]. TRAF3 polyubiquitinates and degrades NF-κB-inducing kinase (NIK) restraining non-canonical NF-κB signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 4-1BB signaling influences other compartments of the cellular immune defense like B cells by induction of proliferation and immunoglobulin production [44]. Downstream signaling of 4-1BB involves NF-κB, which is a main target of B cell receptor (BCR) activation [45]. It was shown that induction of 4-1BB on CLL B cells have an effect on the prevention of apoptosis by activating NF-κB signaling [46].…”
Section: Discussionmentioning
confidence: 99%